109k views
4 votes
- (-(2)) =

And explain why please

User Koenyn
by
5.1k points

2 Answers

2 votes

Answer:

- (-(2)) = 2

Explanation:

- (-(2)) = ?

*distribute the first negative sign*

- (-2) = ?

*distribute the second negative sign*

? = 2

*Two negatives make a positive so the answer is positive 2 : )*

User Lestat
by
5.0k points
4 votes

Answer:

2

Explanation:

A negative times a negative is always a positive no matter what it looks like

I hope this helps you :)

-KeairaDickson

User SnowboardBruin
by
5.2k points